Techniques and actions to promote domestic agri-food products on foreign markets - BURBULEA Rodica; MOROI Elena (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The purpose of this research is to identify the techniques and actions for the promotion of domestic agri-food products on foreign markets. Promotion involves communication with the consumer, not necessarily directly, but with the aim of positively influencing his wishes or actions. On international markets, it is often difficult to coordinate the promotion strategy with the other marketing strategies due to the high degree of variability of promotion tools and because, however, culture, customs and language differences also complicate the promotion activity. The promotion of agri-food products on foreign markets includes a set of actions and means aimed at informing and attracting potential buyers in order to satisfy their needs and desires and, implicitly, to increase the economic efficiency of the activity of the producing enterprises.